Benefits and costs of adopting international financial reporting standards - Nguyen, Van Thi Hong; Nguyen, Co Trong; Mai, Anh Ngoc; Dao, Ha Ngoc (International Journal of Management and Sustainability, 2023)
The application of international financial reporting standards (IFRS) plays an important role in improving the quality of enterprises’ financial statements. At the same time, adopting IFRS makes it easier for companies to access foreign capital. Therefore, the use of IFRS is indispensable for Vietnamese enterprises, especially for companies listed on the stock market. This study was conducted to evaluate the effects of benefits and costs on Vietnamese enterprises’ choice to adopt IFRS. The research surveyed 157 companies. The results of regression analysis using Statistical Package for Social Sciences (SPSS) software show that benefits have a positive impact on Vietnamese companies’ decision to adopt IFRS. On the other hand, costs have a negative impact on IFRS adoption. Based on the results of this study, the trade-off theory is used to explain the relationship between the costs and benefits of applying IFRS. When businesses find that the costs are too great for the company or are not yet balanced by the benefits, they do not apply IFRS. Therefore, business leaders have a correct understanding of the difficulties and challenges of converting to IFRS and have a scientific, methodical, and clear plan and roadmap for the transformation. The authors also offer some suggestions for improving the application of IFRS.